Climate Security as Human Right in South Asia: A Neglected Dimension (Journal of Asian Development Studies, 2025)
In particular, regions such as South Asia are highly vulnerable to the effects of climate change, which pose a significant threat to economic and environmental systems and to fundamental human rights. The intersection of human rights within strategy and security discourses remains inadequately theorised and operationalised in South Asia, despite the concept of climate security gaining significant traction in recent years. This paper argues that climate security should be understood as a fundamental human rights issue in South Asia. It goes beyond normative human rights frameworks currently in place and incorporates the empirical significance of climate induced vulnerabilities. To establish a conceptual framework that illustrates how breaches of climate security manifest as violations of human rights — specifically the rights to life, health, food, water, shelter, and labour —the article uses a qualitative methodology that involves examining the literature and secondary data. In this context, the focus is on South Asian countries, including India, Pakistan, Bangladesh, Nepal, Bhutan, Sri Lanka, and the Maldives, with particular attention to human rights, climate justice, and security. The primary findings indicate that there has always been a disparity between what people claim to believe and what they actually do, particularly for marginalized groups such as women, children, people with low incomes, and climate migrants. The article recommends incorporating human rights-based approaches into climate-security governance, strengthening regional cooperation, and giving communities greater power.